Educação de surdos : o discurso da inclusão educacional produzido por surdos e ouvintes - Santos, Marcos Roberto dos (2017)
In recent years, social inclusion policies have gained a large proportion in our country and, consequently, the education also assumes this inclusive character. Regarding the deaf, it can be seen that inclusive education has different meanings, because the discursive formation of the hearings who have promoted these policies of educational inclusion is in disagreement with the discursive formation of the brazilian deaf community. For the understanding of these discursive formations it was used, mainly, studies of researchers such as Capovilla (2006, 2012, 2016), Quadros and Karnopp (2004), Quadros (2004, 2006), Ferreira (2010), Strobel (2015) and others. As theorical-analytical referential, we adopted the French Discourse Analysis with theorists such as Pêcheux (2014), Mussalin (2001), Fuchs (1997), Orlandi (2013) and others. The corpus analyzed was consisted of legislation, documents, videos, interviews, posters and leaders’ speeches of the deaf movements. In the analysis, it was possible to notice that according to the proposals of the Ministry of Education, deaf students must study in regular schools, with the presence of translators/interpreters of Brazilian Sign Language and have the right to attend the Specialized Educational Attendance in the opposite shift of the class. Thus, the deaf can be inserted into the hearing society and avoid the formation of segregationist spaces. On the other hand, the brazilian deaf community require to have a specialized school where the sign language occupies the function of first language and the language oralized as second, in the written mode. In this context, educational inclusion provides a devaluation of the deaf culture and its linguistic identity. Thus, it is possible to notice that this discursive formations establish relations with different conceptions about the deafness. Thus, this work sought to contribute to the understanding of how the meaning effects of educational inclusion work in the discourses of inclusive policies and of the deaf community. Keywords: Discursive formation. Discourse. Educational inclusion. Deaf community. Bilingual education.